Female genital mutilation/cutting in Africa - Odukogbe, Akin-Tunde A.; Afolabi, Bosede B.; Bello, Oluwasomidoyin O.; Adeyanju, Ayodeji S. (Translational Andrology and Urology; Vol 6, No 2 (April 29, 2017): Translational Andrology and Urology (Global Urology), 2017)
Female genital mutilation/cutting (FGM/C) is a traditional practice in which the external female genitalia is partially or totally incised or excised for a non-therapeutic reason, usually without the consent of the individual. FGM/C is common in Africa with varying prevalence in different countries, though the incidence is reducing because it is considered a human rights issue with tremendous advocacy for its elimination by mainly nongovernmental organizations. It is mainly underreported in many countries in Africa especially where it has been declared illegal. FGM/C is often performed by a nonmedical practitioner with the aim of fulfilling religious or cultural rites and sometimes for economic benefits with the resultant acute, intermediate and late complications. It is sometimes performed by medical practitioners when it is speciously believed that its medicalization reduces the complications associated with the practice. The sensitivity of FGM/C is amplified when compared to male circumcision and voluntary alterations of the female external genitalia like piercing and tattooing as similar practices. The magnitude of the physical and psychosocial consequences of FGM/C outweighs the presumed benefits of the procedures highlighting the need for improvement of the multiple preventive measures by all the stakeholders and in all the sectors.